A Bibliometric analysis on writing and learning outcome research around the world - Kusrin; Wigati, Fikri; lengkanawati, Nenden; Musthafa, Bachrudin (Ethical Lingua: Journal of Language Teaching and Literature, 2023)
This study uses bibliometric analysis to assess the most relevant themes linked to Writing Learning Outcomes, allowing readers to gain a holistic understanding of WLO and the most recent developments in the field. Publication data from Scopus is employed since it is considered as the gold standard for Bibliometric analysis, allowing for the visualization of information concerning the network of nations, keywords, authors, and trends. On September 14, 2022, this study examined 1,053 files spanning the years 1980 and 2022. The findings revealed that the quantity of published works on WLO generally increased, albeit with some years showing a modest decline. Analysing search terms for "Writing Learning Outcomes" (WLO) reveals a central interest in topics including learning goals, assessment, and instructional strategies. Important WLO publications are also discussed in the study. This study presented bibliometric analysis on the relationship between the most prominent themes in WLO research and classroom practice to be used for finding novelty in the area of WLO research.